ANALISIS ISI KARAKTERISTIK DAN SENTIMEN PEMBERITAAN ISU KENAIKAN PAJAK DI KABUPATEN PATI PADA MEDIA ONLINE KOMPAS.COM - Catur Wulan Sari Catur Wulan Sari; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Online news media plays a significant role in shaping public perception of government policies, including local tax policies. The Pati Regency Government under Regent Sudewo raised the Land and Building Tax Assessment Value (NJOP) by up to 250 percent, triggering widespread public resistance and drawing sustained national media attention. This situation makes the coverage patterns of Kompas.com on this issue relevant to examine systematically in order to obtain an empirical picture of how a mainstream national media outlet represents local fiscal policy to its audience. This study aims to describe the characteristics and sentiment of news coverage on the tax hike issue in Pati Regency on the online media platform Kompas.com. The study employed a descriptive quantitative content analysis method with a positivistic approach, following the principles of Klaus Krippendorff. The research object consisted of 44 Kompas.com articles containing the keywords